Dog Beach unleashed - Greenwald, Lisa (Greenwald, Lisa. Seagate summers series, 2016)
Seagate Island's centennial summer should be a huge celebration of beach traditions, but it is the rainiest summer on record and Remy, Micayla, Bennett, and the C Twins find that tempers are short, dogs are bored, and summer magic is hard to find.